Wastewater Treatment Of Sericulture Enterprises With Inorganic Coagulants - A.G.Askarova; S.I.Nazarov; H.K.Razzokov (Peerian Journals Publishing, 2024)
This article describes the effect of the coagulant dose on the specific electrical conductivity, the amount of dry residues and suspended particles during wastewater treatment of sericulture enterprises to the level of process water. At the same time, when treating wastewater from a silk fiber manufacturing enterprise with the proposed coagulants, the efficiency of purification from suspended particles was 95.79%, discoloration was 91%, and dry residue was 81.25%, and the optimal dose of coagulants was calculated based on experimental tests
Keywords: coagulant; wastewater; total hardness; mechanical cleaning